2015
DOI: 10.1007/s10815-014-0413-y
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of gene expression and activity of GRIM-19 affects mouse oocyte viability, maturation, embryo development and implantation

Abstract: Purpose To investigate the expression of GRIM-19 (Gene associated with retinoid-interferon-induced mortality 19) in mouse oocytes and preimplantation embryos, and to study the effect of GRIM-19 on the developmental competence of mouse oocytes and embryos. Methods GRIM-19 was evaluated at both mRNA and protein levels. The expression of GRIM-19 gene was downregulated in mouse oocytes cultured in vitro by specific small interfering RNA (siRNA) injection, while the activity of GRIM-19 was decreased by microinjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Negative: No fluorescence control; Positive: Embryos pretreated with DNAse to ensure TUNEL staining was successful; 5 embryos in each group found in our study, we might presume that the blastocysts derived from heifers after they reach puberty have considerably higher developmental competence, caused by more efficient respiratory chain action. To support the hypothesis that lower expression of NDUFA13 found in the blastocysts derived from oocytes collected from prepubertal heifers accounts for the probable higher lethality of those embryos, expressed by lower blastocyst rate in that group of blastocysts compared to the group from pubertal heifers, we would like to cite the studies of Huang et al [45], Chao et al [46] and Cui et al [47] in mice. In those experiments, it was shown previously that the downregulation of the NDUFA13 gene caused a reduction in mouse oocyte viability, maturation performance, and the developmental and implantation ability of embryos.…”
Section: Discussionmentioning
confidence: 91%
“…Negative: No fluorescence control; Positive: Embryos pretreated with DNAse to ensure TUNEL staining was successful; 5 embryos in each group found in our study, we might presume that the blastocysts derived from heifers after they reach puberty have considerably higher developmental competence, caused by more efficient respiratory chain action. To support the hypothesis that lower expression of NDUFA13 found in the blastocysts derived from oocytes collected from prepubertal heifers accounts for the probable higher lethality of those embryos, expressed by lower blastocyst rate in that group of blastocysts compared to the group from pubertal heifers, we would like to cite the studies of Huang et al [45], Chao et al [46] and Cui et al [47] in mice. In those experiments, it was shown previously that the downregulation of the NDUFA13 gene caused a reduction in mouse oocyte viability, maturation performance, and the developmental and implantation ability of embryos.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown a lack of NDUFA13 leads to the abnormality of the mitochondrion structure, morphology and cellular distribution (Chao et al, 2015;Huang et al, 2004). A deficiency of NDUFA13 leads to a collapse of MMP and an increased apoptosis in HTR-8/SVneo cell line (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…The results of the current study indicated that esophageal tumor cells exhibited reduced Grim-19 mRNA and protein expression compared with normal esophageal epithelial cells. Grim-19 has been associated with reactive oxygen species induced by an IFN/RA pathway and has a conserved evolutionary history in eukaryotic cells (41,42).…”
Section: Discussionmentioning
confidence: 99%